Communication barriers in negotiation - Danilova, E.A.; Zolotuskaya, O.U.; Nazhmiddinova, E.L. (Культура народов Причерноморья, 2005)
This article focuses on the processes by which negotiators influence one another's understanding, beliefs, and outlook – and ultimately, their behavior. In this article the basic structure and process by which information and meaning are transmitted from one person to another are discussed. The objective of this article is to determine how different barriers influence an effective communication.